Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1007/s00436-010-1946-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and expression profiles of Argonaute proteins in Schistosoma japonicum

Abstract: Small non-coding RNAs including microRNAs and small interfering RNAs play important roles in many biological processes of many organisms. Argonaute proteins serve as a key component of the RNA-induced silencing complex for mediating miRNA/siRNA functions. In the present study, we systematically investigated Argonaute proteins in Schistosoma japonicum by using bioinformatics in combination with 5'- and 3'-Rapid Amplification of cDNA ends techniques and thus obtained three full-length cDNAs encoding Argonaute pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 28 publications
(35 reference statements)
1
26
0
Order By: Relevance
“…The expression of SjAgo2 was up-regulated in schistosomula and female parasites, whereas SjAgo3 was highly expressed in schistosomula and male worms. Previously, Chen et al reported that the expression of SjAgo1 was significantly higher in eggs than that in adult worms and the expression of SjAgo2 and SjAgo3 was not significantly different between male and female parasites [27]. This inconsistency is likely due to different experimental conditions, especially the endogenous controls applied in the two studies.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The expression of SjAgo2 was up-regulated in schistosomula and female parasites, whereas SjAgo3 was highly expressed in schistosomula and male worms. Previously, Chen et al reported that the expression of SjAgo1 was significantly higher in eggs than that in adult worms and the expression of SjAgo2 and SjAgo3 was not significantly different between male and female parasites [27]. This inconsistency is likely due to different experimental conditions, especially the endogenous controls applied in the two studies.…”
Section: Resultsmentioning
confidence: 96%
“…In S. mansoni , four Argonaute proteins were identified by two groups mainly based on bioinformatic analysis, but SmAgo3 and SmAgo4 seemed to be generated from an alternatively spliced mRNA [26]. Argonaute orthologs in S. japonicum (SjAgos) have been also reported by two groups [27], [28]. Both of them tried to determine the full-length sequences of the three Argonaute proteins and described the molecular characteristics of SjAgos.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different stages of schistosome development are associated with different categories of miRNAs, suggesting that miRNAs may be involved in the regulation of schistosome development (Krautz-Peterson and Skelly, 2008; Xue et al, 2008; Chen et al, 2010; Hao et al, 2010; Luo et al, 2010; Cai et al, 2011; Simoes et al, 2011). Several lines of evidence also indirectly imply that miRNAs may regulate the pathogenesis of schistosomiasis (Cheng et al, 2013; Hoy et al, 2014).…”
Section: Potential Role Of Schistosoma Mirnas In Worm Development Andmentioning
confidence: 99%
“…First, the key components of miRNA biogenesis, including the Ago proteins (Chen et al, 2010) and Dicer (Krautz-Peterson and Skelly, 2008; Luo et al, 2010), have been shown to be differentially expressed during different stages of schistosome development. Second, some of miRNAs such as miR-36, miR-71, bantam, miR-7, and others, have been shown to specifically express in a specific stage of S. japonicum (Xue et al, 2008; Hao et al, 2010; Cai et al, 2011).…”
Section: Potential Role Of Schistosoma Mirnas In Worm Development Andmentioning
confidence: 99%